Enabling and constraining factors in the management of four City of Cape Town public libraries - Nkhahle, Rethabile A (Library and Information Studies Centre (LISC), 2023)
The world has changed rapidly due to advances in technology. This changing environment has affected the way the libraries are managed. Some public library managers run libraries with little or no management experience. These managers might well struggle to perform their duties effectively and efficiently due to the lack of the necessary skills such as human resources management, conflict management, communication, problem solving and leadership skills needed for the job. This study aimed at finding out the practices which constrained and enabled the management of four City of Cape Town public libraries. The study further looked at ways to improve the management practices in areas where they were doing well and also how to address some of the challenges that were faced by the managers. This was a qualitative study which included four library managers and four assistant librarians based in four City of Cape Town libraries situated in the southern suburbs of Cape Town. Semi-structured interviews were conducted in trying to find out what those practices were. The theory of practice architectures was used to look into these practices. The NVivo computer application was used in the analysis of the results and this helped in identifying the themes in accordance with what the research question and sub-questions required. Practices constraining the managing of the sampled public libraries were found to be: inadequate provision of resources and infrastructure, staffing issues, poor communication and weak conflict management. Practices enabling the management of these public libraries were: staff training and development, providing opportunities for teamwork, following library policies and plans, and commitment to meeting the needs of the communities served. Some of the recommendations made are that the City of Cape Town libraries should look into increasing funding for these libraries so that they can buy more stock for the clients, offer more training for all the employees, support both employees who want to pursue further studies at undergraduate and postgraduate levels, and increase staffing. The study has introduced a new way of looking into practices affecting public library management and that is in terms of the sayings, doings and relatings in the practice architectures model.